Atopic dermatitis in India: prevalence and correlation with personal and family history of atopic diseases. - Agarwal, P.; Saini, A.; Gupta, M.K.; Agarwal, U.S. (European Journal of Pediatric Dermatology, 2014)
Atopic dermatitis (AD) is a chronic, itchy inflammatory skin disease with unknown etiology, although influenced by genetic and environmental factors. This study is aimed at finding out the changing trends in prevalence of atopic dermatitis and its correlation with personal and family history of atopy. A questionnaire based study was carried out among 927 school children aged 4-18 years from November to December 2011. Out of 927 children, 79 (8.52%) had AD with 49 males (62.03%) and 30 females (37.97%). The personal history of atopic diseases was found positive in 47 children (59.49%) and family history in 26 children (32.91%). An isolated personal history of atopic diseases was positive in 30 children (37.97%) while an isolated family history was positive in only 9 children (11.39%). 56 children (70.89%) out of 79 had a positive history of atopic allergic diseases, either personal or family. The female children with isolated personal history of atopic diseases were at a statistically significant (p value = 0.006) risk of developing AD. Moreover, in children with positive personal history of atopic diseases, rhinoconjuctivitis was present in all 47 children while only 9 children had additional wheezing. Atopic dermatitis is still less prevalent in developing countries due to environmental and socio-economic factors.